Comportamento e variação de procedências de Corymbia citriodora em diferentes tipos de solos - Morais, Eurípedes; Zanatto, Antonio Carlos Scatena; de Moraes, Mário Luiz Teixeira [UNESP]; Freitas, Miguel Luiz Menezes; Sebbenn, Alexandre Magno (My University, 2011)
The aim of this study was the selection of Corymbia citriodora provenances for three different kinds of soils occurring in Luiz Antônio Experimental Station, São Paulo, Brazil (Latossolo Vermelho, Areia Quartzosa and Latossolo Roxo). The provenance test was established in 1983, with ten Corymbia citriodora provenances and one Eucalyptus grandis as control, original from a seed production area. The trials were established in a random block design with 11 treatments, three repetition and square plots with 25 trees. In 2008, there were evaluations of height, diameter at breast height (DBH, 1.3 m), stem form and survival. Significant differences among soils and provenances were detected for the growth traits, stem form and survival in all those studied soils. Significant provenance and soil interactions were not detected. All provenances showed higher growth in height and DBH in Purple Latosol. The control had a higher growth rate in relation to highness, DBH and stem form than Corymbia citriodora provenances in all the studied soils, but it presented, generally, a lower survival rate than Corymbia citriodora provenances. Pederneiras (11) Corymbia citriodora provenance presented a higher performance in relation to highness and DBH in all kinds of soils, and Gilgandra (4) provenance, original from Australia, had the worst development. Therefore, Pederneiras (11) provenance is, therefore, the best choose for reforestations in all those studied soils.
The behavior and provenance variation of Corymbia citriodora in different kinds of soil
Keywords: Corymbia; Provenance test; Soil; Tree breeding; Corymbia citriodora; Eucalyptus; Eucalyptus grandis